(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Assessing the success of Information Systems (ISs) has been identified as one of the most critical issues in IS field. Offering more services and the ease of access is considered as a significant factor for today’s academic environments. E-learning systems are having an exquisite impact over the success of academic environments by reducing the costs and time of training students, by providing an integrated place where students can have access to it for finding their desired materials and to share the knowledge properly among the students and the lecturers. To implement effective e-learning systems, assessment of the quality of these systems has become an important issue. This study identifies the significant factors that influence on successes in e-learning systems. Hence, we use two powerful techniques from Multiple Criteria Decision Making (MCDM) and Artificial Intelligence fields. Using fuzzy TOPSIS, we rank the factors using a pair-wise questionnaire. Then, to get the real level of factors, we perform the fuzzy logics using a 5-likert questionnaire. Results of assessing show that the system quality is very important factor in relation to the service quality, information quality and learning community.